A recombinant trivalent vaccine candidate against human adenovirus types 3, 7, and 55. Issue 16 (12th April 2018) - Liu, Tiantian; Zhou, Zhichao; Tian, Xingui; Liu, Wenkuan; Xu, Duo; Fan, Ye; Liao, Jiayi; Gu, Shujun; Li, Xiao; Zhou, Rong
Highlights: Successful construction of a recombinant trivalent adenovirus vaccine rAdMHE3-h55. rAdMH3-h55 can induce NAbs against HAdV-3, HAdV-7 and HAdV-55 in mice. rAdMHE3-h55 can protect mice from infections of HAdV-3, HAdV-7 and HAdV-55. The method of construction rAdMHE3-h55 can be further explored to develop vaccines. Abstract: Human adenoviruses types 3 (HAdV-3), 7 (HAdV-7) and 55 (HAdV-55) are major pathogens of acute respiratory infections (ARI) in children and adults. More than one type of HAdV can infect patients simultaneously, and the infections are sometimes fatal. However, there is currently no vaccine approved for general use in children and adults. Thus, development of a multivalent HAdV vaccine to combat HAdV infection becomes imperative. In this study, we constructed a new recombinant trivalent human adenovirus vaccine (rAdMHE3-h55), which expresses the hexon protein of HAdV-55 in the E3 region of rAdMHE3, a previously prepared bivalent vaccine candidate against HAdV-3 and HAdV-7. The results of in vitro neutralization assays indicate that rAdMHE3-h55 can induce the production of neutralizing antibodies against HAdV-3, HAdV-7, and HAdV-55 in mice. Furthermore, immunization with the recombinant trivalent vaccine candidate completely protected the mice challenged with HAdV-3, HAdV-7, orHAdV-55, respectively, showing lower lung viral loads and less lung Pathological changes was compared with those in unvaccinated mice. The current findings contribute to the development of a new adenovirus vaccine candidate and also advance this construction method for the generation of recombinant adenovirus vaccines. In conclusion, our recombinant trivalent vaccine rAdMHE3-h55 can provides protection against challenge with HAdV-3, HAdV-7, or HAdV-55 in mice. Future work of optimizing this vaccine candidate may lead to a more effective way of preventing respiratory diseases caused by common human adenoviruses.